Guardianes de la real justicia: alcaldes de indios, costumbre y justicia local en Huarochirí colonial - Puente Luna, José Carlos de la (2016)
This essay examines the local construction of law in San Damián de Urotambo—an indigenous community in Huarochirí—in the early seventeenth century. In Andean towns, the alcaldes (magistrates), commonly members of the local nobility, had jurisdiction over dispute resolution and made use of Castilian law. These alcaldes, representatives of royal power, were central actors in the circulation of legal knowledge. They were also experts in the usage of Castilian judicial and notarial practices. Likewise, litigants were key agents in the process of creating a new juridical order by invoking both European and Pre-Columbian juridical traditions. This essay illustrates how these two legal spheres—Castilian and Andean—mingled and were negotiated by judges and litigants through a process of interlegality. These legal agents played a crucial role in the making of colonial law within the plural dimensions of the juridical world of San Damián de Urotambo.